2018
DOI: 10.1007/s13244-018-0621-6
|View full text |Cite
|
Sign up to set email alerts
|

The amount of calcifications in pseudoxanthoma elasticum patients is underestimated in computed tomographic imaging; a post-mortem correlation of histological and computed tomographic findings in two cases

Abstract: ObjectivesPseudoxanthoma elasticum (PXE) is a rare genetic disorder, characterised by elastic fibre degeneration and calcifications in multiple organ systems. Computed tomography (CT) imaging is a potential method to monitor disease progression in PXE patients; however, this method has not been validated. The aim of this study was to correlate histological and computed tomographic findings in PXE patients to investigate the ability of CT scanning to detect these alterations.MethodsPost mortem total body CT sca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 20 publications
0
12
0
Order By: Relevance
“…PPi is one of the strongest inhibitors of ectopic calcification and therefore PXE results in extensive calcification of the elastic fibers in the skin, the Bruch's membrane of the eyes, and the peripheral arteries [7]. The arterial phenotype involves medial arterial calcification of predominantly the intracranial arteries and the arteries of the legs, but other arteries, including the carotid arteries, aorta and iliac arteries are also affected by vascular calcifications [8,9]. PXE can therefore be used as a model disease to investigate the role of relatively isolated medial arterial calcification on vascular physiology and function and the effect of arterial stiffness on end organ damage [10].…”
Section: Introductionmentioning
confidence: 99%
“…PPi is one of the strongest inhibitors of ectopic calcification and therefore PXE results in extensive calcification of the elastic fibers in the skin, the Bruch's membrane of the eyes, and the peripheral arteries [7]. The arterial phenotype involves medial arterial calcification of predominantly the intracranial arteries and the arteries of the legs, but other arteries, including the carotid arteries, aorta and iliac arteries are also affected by vascular calcifications [8,9]. PXE can therefore be used as a model disease to investigate the role of relatively isolated medial arterial calcification on vascular physiology and function and the effect of arterial stiffness on end organ damage [10].…”
Section: Introductionmentioning
confidence: 99%
“…Studies of human and mice found an increased carotid intima media thickness [22][23][24] due to ABCC6 deficiency, which correlates with higher risk for cardiovascular complications 25 . In current case reports it has been noticed that PXE patients suffer from degenerated and calcified elastic fibers in heart tissue as well stenosis in coronary arteries 26,27 . Furthermore, in a cardiac ischemia-reperfusion injury mice model could be demonstrated that the infarct size in heart tissue was increased in Abcc6 −/− mice 28 .…”
Section: Discussionmentioning
confidence: 98%
“…According to Gheduzzi et al the lung was more severely affected than digestive system or kidneys. Vos and Krankenburg et al found degenerated elastic fibers in the pleura of two patients with PXE [22]. Lately, these reports were the subject of a study by Pingel et al who interpreted reduced levels of DLCO % as a lead on restrictive lung disease.…”
Section: Discussionmentioning
confidence: 98%